1971
DOI: 10.1002/ajpa.1330340308
|View full text |Cite
|
Sign up to set email alerts
|

Maturation disparity between hand‐wrist bones in Hong Kong Chinese children

Abstract: The hand-wrist radiographs of 571 Chinese boys and girls from Hong Kong, 2 months to 17 years old, were assessed centerby-center according to the Greulich-Pyle Atlas. For each child the mean skeletal ages (SA) of six bone groups with each group consisting of bones from the same rows, were recorded. The overall SA was also obtained as the arithmetic mean of all centers.Maturation disparity between the various bone groups was demonstrated with the two proximal rows (distal radio-ulna, carpals) more retarded, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

1971
1971
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
1
7
0
1
Order By: Relevance
“…Our findings were somewhat similar to those of Lee ( 14 ), who applied the manual GP atlas to assess children from Hong Kong in China in the 1970s. They reported that the middle and distal phalanges tended to be relatively advanced, followed by the metacarpals, proximal phalanges and distal radius-ulna.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings were somewhat similar to those of Lee ( 14 ), who applied the manual GP atlas to assess children from Hong Kong in China in the 1970s. They reported that the middle and distal phalanges tended to be relatively advanced, followed by the metacarpals, proximal phalanges and distal radius-ulna.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, according to the anatomical differences and related references, five groups were defined, each of which consisted of bones from the same row, to further clarify the maturation disparity ( 5 13 14 ). The groups were as follows: 1) distal radius and distal ulna; 2) the first, third and fifth metacarpals; 3) the first, third and fifth proximal phalanges; 4) the third and fifth middle phalanges; and 5) the first, third and fifth distal phalanges.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Respecto a esto, Kelly (1995) establece que el tiempo entre nacimientos es el factor más influyente en la fecundidad para este tipo de poblaciones. Los cazadores-recolectores necesitan tener intervalos largos entre nacimientos debido a la energía que insume el cuidado de niños durante la lactancia prolongada y la necesidad de cargarlos durante los procesos de movilidad grupal (Lee 1971;Sussman 1972). Si bien en una primera instancia se consideró la lactancia extendida como la principal causa del espaciamiento entre los nacimientos, el avance de las investigaciones permitió conocer que la lactancia suprime la ovulación solo durante los primeros 18 meses, alejándose del intervalo mínimo de 36 meses establecido para los cazadores-recolectores (Menken 1975).…”
Section: Discussionunclassified
“…The developmental heterogeneity of the individual bone centres in the hand and wrist (Lee, 1971;Pyle, Mann, Dreizen, Kelly, Macy and Spier, 1948) has usually been regarded as a nuisance in attempts to arrive at overall assessments of skeletal age, necessitating as it does the scrutiny of a great number of individual centres in order to arrive at some sort of stable average. The present study is an inquiry into these discrepancies, to see whether they may be exploited as contributions to the reliability of assessment of skeletal age.…”
Section: Introductionmentioning
confidence: 98%